DEVELOPMENT OF AUDIO VISUAL MEDIA TO IMPROVE FARDU KIFAYAH SKILLS IN FIQH LEARNING IN PHASE E CLASS X OF STATE SENIOR HIGH SCHOOL I PADANG LAWAS - Fitriani Siregar; Muhammad Darwis Dasopang; Abdusima Nasution (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The process of learning Fiqh, specifically the material on fardu kifayah, is not fully facilitated by the presence of textbooks alone, which only provide theoretical content to students. There is no direct practice due to insufficient time. The research problem formulated in this study is: How is the initial research of Audio-Visual Media for Fiqh Learning on Fardu Kifayah for Class X students at Madrasah Aliyah Negeri I Padang Lawas? What is the validity level of the Development of Audio-Visual Media to Improve Fardu Kifayah Skills for Class X students at Madrasah Aliyah Negeri I Padang Lawas? What is the practicality level of the Development of Audio-Visual Media to Improve Fardu Kifayah Skills for Class X students at Madrasah Aliyah Negeri I Padang Lawas? What is the effectiveness level of the Development of Audio-Visual Media to Improve Fardu Kifayah Skills for Class X students at Madrasah Aliyah Negeri I Padang Lawas? This research is a Research and Development (R&D) study with stages including analysis, design, development, implementation, and evaluation. The study was conducted at Madrasah Aliyah Negeri I Padang Lawas. The subjects of this study were 38 students of class X IIS 1, consisting of 14 males and 24 females. Data collection techniques included observation and questionnaires. The validation results in this study indicate that the audio-visual media validation by material experts is 94%, declared valid and usable after revision, and the media validation result is 90%, declared valid and usable after revision. The response of the Fiqh subject teachers was 90%, and the response of the curriculum teachers was 88%. The response of the students to the audio-visual media was 90%. The results of this study indicate that the audio-visual learning media for the Fiqh subject, implemented in class X IIS 1, showed an improvement in test scores from a pre-test score of 52.23% to a post-test score of 91.44%. Therefore, using this audio-visual media resulted in an increase of 39.21% from pre-test to post-test scores. It can be concluded that the audio-visual media for the Fiqh subject is suitable for use and can improve student learning achievement.